Time-series evidence on the sources of trends in wage inequality - Ramey, Valerie; Borjas, George J. (American Economic Review, 1994)
Changes in wage inequality have long been a concern of labor economists and public policymakers. When the wage premium for college graduates fell during the first half of the 1970's, many researchers blamed the decline on the increase in the relative supply of college graduates. When the college wage premium increased dramatically during the 1980's, researchers offered a variety of explanations, such as skill-biased technological change and the internationalization of the U.S. economy. In this paper, we use time-series analysis to evaluate the most common explanations given for the trends in wage inequality. Using cointegration techniques, we evaluate the link between the trends in the candidate explanatory variables and wage inequality. We show that the only variable that consistently shares the same long-run trend with our wage-inequality series is the durablegoods trade deficit as a percentage of GDP. This variable not only follows the same trend as wage inequality during most of the 1980's, but also for the period from 1949 to 1979. No other single explanation shows the same long-run consistency. I. An Analysis of Trends in Wage Inequality